Non-Template Synthesis and Antimicrobial Activities of Tetraazamacrocyclic Ligands with Variable Ring Sizes - NIRDOSH PATIL; RAMACHANDRA AKKASALI (International Journal of Pharma and Bio Sciences, 2010)
Three new macrocyclic ligands containing four aza groups have been prepared by the condensation reaction of 1-(2, 4-dihydroxyphenyl)-3-phynyl propane-1,3-dione with different diamines (1,2-diamino ethane, 1,3-diamino propane and 1,2-diamino benzene). The macrocycles prepared are “1,9-(2,4dihydroxyphenyl)-1,2-diphenyl-1,5,8,12-tetraazacyclotetradeca-1,4,z8,11-tetraene”, “4,10-di(2,4dihydroxyphenyl)-2,12-diphenyl-1,5,9,13-tetraazacyclohexadeca - 1,4,9,12-tetraene” and dibenzo-[b,I]4,9-di(2,4-dihydroxyphenyl)- 2, 11 -diphenyl - 1,5,8,12-tetraazacyclotetradeca-1,4,8,11-tetraene”. All the macrocyclic ligands were characterized by elemental analysis and IR, UV, NMR and mass spectral investigations and have been screened in vitro for their possible antimicrobial activity.